A study on the utilization of steel slag in concrete - Arslan, Ehat Giray. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
Steel slag is a by-product of the steel production. The scope of this thesis is to investigate the effect of steel slags, using as replacement of Portland cement, on the physical and mechanical properties of mortars and concretes. Four different types of steel slags were used in this study, all of them were obtained from Basic Oxygen Furnace of ERDEM R- Eregli Iron and Steel Plant as a by product. Steel slags were ground into cement fineness at Akçansa Cement Laboratory. These ground steel slags replaced standard portland cement in specified ratios (20, 40 and 60 % in mass) and 12 types of slag added cements were gained in total. First, the cementitious properties of Erdemir steel slags and the effect of steel slag addition on the properties of Portland cement were investigated in accordance with relevant codes. Density, w/c ratio, setting time, soundness, activity indices and strengths of slag added cements were determined. Then, concretes with a constant water/binder ratio and similar type aggregates were produced with 12 slag added cements. Physical and mechanical tests were conducted on concretes produced with steel slag added cements. Both cement and concrete tests were conducted compared with reference cement and concrete samples and all results are given in comparison. According to the test results, it was seen that the ERDEM R steel slags did not meet the required activation properties. In cement tests, as ratio of the replacement of Portland cement by steel slags increased, it was observed that, water requirement, setting times, compressive and flexural strengths decreased, however, soundness values increased. Similar to that, in concrete tests, it was determined that as the ratio of the replacement of portland cement by steel slags increased, compressive and flexural strengths decreased dramatically, however, rapid chloride diffusion, probably because of the metal content in steel slag, increased. Only in two types of steel slag with a replacement ratio of 20%, results mentioned above had the nearest values to the reference mortar and concrete samples. Also it wass examined that the type of steel slag or the replacement ratio did not have any effect on fracture energy.
Keywords: Slag.; Concrete -- Additives.